PENINGKATAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN IPA MELALUI PENDEKATAN INKUIRI DI SD - Kiswanto, Heri; ., Fadillah; ., Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Improved Student Learning Activities Learning Science Through the Inquiry Approach in the primary is the title of this study aimed to reveal the existence of significant influence between inquiry approach to learning activities of students in the sixth grade at SDN 26 River Ambawang Kubu Raya district. The method used in this research is descriptive method to form a class action research. Election inquiry approach to learning science in the classroom because learning approach is deliberately designed to enhance students' learning activities through a process of self discovery. After in applied inquiry approach in the process of learning science in the classroom, it increases students' learning activities. This is evidenced by an increase in student learning activities in the first cycle increased by 46% to 76% in the second cycle. With the increase in students' learning activities, the results of student learning is increasing. Thus, the application of an inquiry approach to learning of Natural Sciences in the sixth grade at SDN 26 River Ambawang Kubu Raya district can improve student learning activities. Keywords: Inquiry Approach Improve Learning Activities. Abstrak: Peningkatan Aktivitas Belajar Siswa Pada Pembelajaran IPA Melalui Pendekatan Inkuiri di SD merupakan judul penelitian ini yang bertujuan untuk mengungkap adanya pengaruh yang signifikan antara pendekatan inkuiri terhadap aktivitas belajar siswa di kelas VI SDN 26 Sungai Ambawang Kabupaten Kubu Raya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan bentuk penelitian tindakan kelas. Pemilihan pendekatan inkuiri dalam proses pembelajaran IPA di kelas karena pendekatan pembelajaran ini memang sengaja dirancang untuk meningkatkan aktivitas belajar siswa melalui proses penemuan sendiri. Setelah diterapkanya pendekatan inkuiri ini dalam proses pembelajaran IPA di kelas, ternyata aktivitas belajar siswa meningkat. Hal ini terbukti dengan adanya peningkatan aktivitas belajar siswa pada siklus I sebesar 46% meningkat menjadi 76% pada siklus II. Dengan adanya peningkatan aktivitas belajar siswa tersebut, maka hasil belajar siswa juga turut meningkat. Dengan demikian, penerapan pendekatan inkuiri pada pembelajaran Ilmu Pengetahuan Alam di kelas VI SDN 26 Sungai Ambawang Kabupaten Kubu Raya dapat meningkatkan aktivitas belajar siswa Kata kunci : Pendekatan Inkuiri Meningkatkan Aktivitas Belajar.